Implementasi Blockchain Menggunakan Multi-Signature Approval dan Merkle Tree untuk Sistem E-Voting Pemilu - Villeneuve Andhira; Yudi Wibisono; Rizky Rahman (LKP KARYA PRIMA KURSUS, 2026)
The implementation of conventional general elections in Indonesia still faces significant challenges, including high logistical costs, risks of data manipulation, and a lack of process transparency, which triggers public distrust. This research aims to design a future e-voting system prototype by proposing a Hybrid Voting Framework based on Ethereum blockchain technology and the InterPlanetary File System (IPFS). Scalability and privacy issues are addressed through the integration of the Merkle Tree data structure, where only a 32-byte root value is stored on-chain, while sensitive data is managed off-chain. To mitigate the risk of authority centralization, the system implements a concept from Proof of Authority (PoA) consensus mechanism with a multi-signature approval scheme, requiring the consensus of the majority of validators (>50%) for every administrative action. The test results show that the system is capable of maintaining voting integrity through the one-person-one-vote principle with a stable block creation time of under 10 seconds. Furthermore, the Recent Activity Log and